COMPARISON OF TREATMENT WITH TACROLIMUS 0.03% AND SUPEROXIDE DISMUTASE AND CATALASE IN VITILIGO - Paracha, Mohammad Majid; Khurshid, Khawar; Pal, Sabrina Suhail; Ali, Zafar (Journal of Postgraduate Medical Institute, 2011)
Objective: To compare the efficacy and safety of topical tacrolimus 0.03% with superoxide dismutase and catalase in vitiligo. Material and methods: This hospital based quasi-experimental study was carried out in out patients department of Dermatology Unit-II, Mayo Hospital Lahore in year 2006-2007. Patients were selected by non-probability purposive sampling method after obtaining an informed consent. Both sexes (above 5 years) were included with head and neck vitiligo. They were randomly divided into 2 groups; group 1: superoxide dismutase and catalase; group 2: tacrolimus by using random number table. Results: There were 34(56.7%) females and 26(43.3%) males. Age of the patients ranged from 5 to 60 years with the mean age of 20.52+14.34 years. Overall 31(62%) patients showed repigmentation of varied grades. Repigmentation was shown by 14(46.6%) patients in superoxide dismutase & catalase group and 17(56.6%) patients in tacrolimus group. Conclusion: Topical superoxide dismutase & catalase and tacrolimus are effective treatment modalities in patients with vitiligo. There is no significant difference regarding efficacy and safety between both forms of treatment.